(untitled) - Williams, Anneli (Thành phố Hồ Chí Minh, 2015)
The Vocabulary for IELTS book and CD cover vocabulary items and skills which are relevant to all four exam papers: Listening, Reading, Writing and Speaking. In each unit, you work towards an exam practice exercise which is modelled on the actual IELTS exam. Each unit contains activities that help you develop, step-by-step, the vocabulary knowledge and skills to help you tackle the exam. Exam tips throughout the book highlight essential vocabulary-related learning strategies and exam techniques.
Keywords: English language,Tiếng Anh; Examinations,Kỳ thi